I am Princess X - Priest, Cherie (Arthur A. Levine Books, an imprint of Scholastic Inc., 2015)
Years after writing stories about a superheroine character she created with a best friend who died in a tragic car accident, sixteen-year-old May is shocked to see stickers, patches, and graffiti images of the superheroine appearing around Seattle.